PENGATURAN INVESTASI SEMI KELOLA DI BIDANG PERDAGANGAN JASA AKOMODASI WISATA - Shintyani Brahmisiwi, Ida Ayu; Retno Murni, R.A.; Udiana, I Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 2 No 2 (2017)DO - 10.24843/AC.2017.v02.i02.p013, 2017)
There are many business activities in the tourism industries in Indonesia. One of them is the provision of services, specifically in Bali. The tourists, who are traveled to Bali, have a desire to invest. Practically, in the provision of services, there are many variants of the business which are not easy to be categorized as a services trading in tourism. It has been mixed with other business variants beyond the tourism services. One of its variants is the development services and the management of property. It was developed with the business scheme and managed with the management of property scheme. The problem is, the seller or the developer offer a tourism accommodation services. The other problem is that property, which has been developed, financed by the foreign buyer. The property is managed by the developer for the provision of tourism accommodation service purposes. Further, the owner of the property got an income from the property management. The parties of this investment model expect that income as a return of their investment. This business model is usually called the return on investment in the tourist accommodation trading services. The type of this research, which used for this thesis, is normative research. It’s researched from The Investment Constitution, the Tourism Constitution, The Construction Services Constitution and some of regulations related with the arrangement of the return on investment. This research was used material sources of law, which are primary legal materials, secondary legal materials and tertier legal material. The result of this research show that the rules about return on investment in the tourist accommodation trading services are not regulated explicitly. The regulation hasn’t been reached that return on investment activities. It causes lot of losses for the foreign investor. The government and the society also get same troubles.